Coexistence of Aphid Predators in Cacao Plants: Does Ant-aphid Mutualism Play a Role? - Evandro do Nascimento Silva; Ivette Perfecto (Sociobiology)
Mutualism between ants and hemipterans that produce honeydew has important implications for biological control because hemipterans defended against predators can reach economic injury levels. We tested the hypothesis that ant-aphid mutualism can mediate competition and promote the coexistence of aphid natural enemies. A quadrate in the field measuring 30 x 30 meters (10 plants in 10 rows = 100 plants) was established in a cacao plantation and a whole quadrate survey was carried out in vegetative shoot flushings from the trunk. The number of ants and predators, the identity of ant and natural enemy species and colony occupancy by ants were recorded. Spatial association indexes were used to evaluate the degree of overlap in ant-ant and ant-predator spatial distributions. The ant Crematogaster victima F. Smith was selected for a test on differences in its attack behavior against larvae of the syrphid Ocyptamus antiphates (Walker) and a species of ladybird beetle (Coleoptera: Coccinelidae). Five species of ants were found tending aphids more frequently and their level of spatial association was slightly negative with remarkable mutual exclusion from aphid colonies. Two of them, Cr. victima and Cr. erecta Mayr, were potential defendants of aphids and were selected to study their spatial association with the distribution of natural enemies. It was found that spatial association between ants and aphid predators is slightly positive. The results suggest that the occurrence of attack behavior of Cr. victima against syrphids, but not against coccinellids, can increase coexistence of predators by generating independent spatial distribution.